Etnik Tionghoa di Indonesia - Wibisono, Lily; Intisari Mediatama, PT. (Jakarta : Intisari Mediatama, 2006)
The Chinese in Indonesia
Keywords: Chinese -- Indonesia; Chinese -- Indonesia -- Social life and customs